Assessing Biology Practical Lessons in Some Selected Colleges of Education in Ashanti Region of Ghana (International Journal of Scientific Research and Management (IJSRM), 2018)
The study investigated how biology practical lessons are conducted in some selected Colleges of Education in Ashanti Region of Ghana. The sample population was made up of 60 students and 12 biology tutors from six selected Colleges of Education. The main instrument used for the study was questionnaire. Data collected were analyzed using frequency counts and percentages. The research findings showed that both tutors and students from the selected science colleges considered practical lessons as one of the effective means of teaching and learning biology. It also came out that, the tutors’ pre-activities and teaching strategies in selected science and non-science colleges of education were not different. Again, students from the science colleges tend to have a greater advantage over their counterparts from the non-science colleges, because they were exposed to some other additional strategies. Background to the Study The upgrading of the teacher education certificate programme to diploma advocated the conventional approach to science practical activities and suggested that science practical work should be laboratory based. To achieve this goal, all Colleges of Education had to be provided with laboratories well-resourced with adequate equipment and apparatus. Unfortunately, however, a close observation made about some Colleges of Education in Ghana, revealed that they do not have standard laboratory stocked with adequate equipment and apparatus. Even those having standard laboratories for science teaching, such laboratories were ill-equipped. Other series of observations made about some Colleges of Education also showed that the approach currently being used to teach biology is most often based on classroom work which is intended only to meet examination requirements. Meanwhile, practical work is known to be an essential component of studying the natural environment. It is often defined as a typical laboratory work where students encounter ideas and principles at first hand. The “hand-on approach has the potential to stimulate students’ interest in the subject matter, teach laboratory skills, enhance the acquisition of knowledge, and give insight into scientific attitudes and objectives. Practical work, according to Beatty and Woolnough (1982) is usually done in school science for several reasons. Some of these reasons are to make phenomena more real through experience and to develop certain critical and disciplined attitude. It is also done to develop specific manipulative skills and to elucidate theoretical work as an aid to comprehension (Beatty & Woolnough, 1982). All these benefits are lost if biology lessons follow literary approaches only. Though practical lessons are to be used by tutors to help their students to achieve better results in biology, it was sad to find that in most of the colleges, the biology laboratories were used for theory lessons but not practical lessons. This is because the laboratories were ill-equipped with materials and equipment necessary for practical lessons (Serwaa, 2007). Although, some studies have been conducted in the past years to investigate the issue in the study area, still there seemed to be a growing concern about the deficiency in biology practical lessons in some Colleges of Education. It is for these reasons that this study investigates and compares how biology practical activities are done in some selected Colleges of Education in Ashanti region.